Pendekatan Persuasif untuk Generasi Digital yang Terampil dan Produktif di Kampung Sukorame Mangunan Yogyakarta - Dyaloka Puspita Ningrum (Universitas Muhammadiyah Semarang, 2022)
The generation of digital natives has become a new term that is already quite popular in the ears of the public, especially for those who were born in the midst of the development of the internet and the digital world. Social media is even one of the products of the growth of digitalization which has been transformed as an alternative media with all its benefits. However, it cannot be denied, the existing phenomenon shows that users tend to ignore the ethics of media itself. So that a persuasive approach is needed, especially for those who are still very young, including the youth group in Kampung Sukorame Mangunan, Yogyakarta. This activity was attended by 20 participants consisting of youths aged 16-30 years with the aim that the group can become human resources capable of facing competition in the current creative industry. Using the lecture method, question and answer and direct practice, the participants are invited to be more productive with a number of discussion topics such as: interesting strategies in making curriculum vitae, creating podcast content as an alternative communication medium, as well as procedures for writing popular opinions that are packaged in such a way and delivered communicatively. possible. The results of the activity show that there is an urgency for the participants at the location because they have never received an approach as well as training, especially regarding digital literacy, which even most of the people interact with every day in the digital realm itself. This community service is expected to be a manifestation and serious effort in developing young people's soft skills in a sustainable digital era.